On the Reasonableness of Religious Belief according to W. James' "The Will to Believe" with reference to Alvin Plantinga's “The Nature of Necessity” - Nakhla, Maria Gadelrad Shenouda (AUC Knowledge Fountain, 2026)
Analytically, I follow William James's approach in his paper "The Will to Believe" to demonstrate that holding a religious belief is reasonable and it is not incompatible with being a philosophy scholar. I do this through explaining the way James addressed the main obstacle that Clifford puts against belief (in general) which is ‘the lack of sufficient evidence’. Clifford claims that belief cannot be accepted without evidence on it. James breaks apart this obstacle through many steps. First, analyzing the nature of belief itself, showing that belief cannot be attained based on intellectual grounds alone (which needs sufficient evidence), but a belief is a sum of many elements, such as man’s desires, fears, hopes, passions, as well as the social impact (he calls all these elements ‘passional nature’). Then, James explains a second important issue that affects the process of belief-formation, which is our approach to true belief. He discusses different approaches to truth, defending the pragmatic approach which relates true belief to deeds. He, then, moves to a crucial point: the reason religious beliefs are considered unreasonable lies in the fact that people are not always able to support them with objective evidence. However, James emphasizes that the nature of religious belief is different from that of scientific belief. It is reasonable for scientific belief to rely on objective evidence (since scientific belief relies more on the intellectual part), because the evidence already exists—it is fully present, while religious beliefs are still in the realm of the possible, thus, how can one refer to reality to verify them? Here, Plantinga explains this further through "possible worlds," explaining that reality, the actual world, can be replaced by another possibility to become the new reality, as long as this shift occurs to possible not necessary propositions. This means that what is not ‘actual’ today may be ‘actual’ tomorrow. This explains our inability to find objective evidence for religious beliefs, because they are within the realm of possibility, not yet actual. The issue, then, is not that religious beliefs are unreasonable, but rather that the order is different. Belief comes first, then evidence comes after belief becomes actual. However, religious belief requires a willing choice because man holds a belief that has no evidence in reality yet, and that is why James accurately named his paper ‘The Will’ to Believe.